The effects of conjugated linoleic acid supplementation on lipid profile in adults: A systematic review and dose–response meta-analysis - Asbaghi, Omid; Ashtary-larky, Damoon; Naseri, Kaveh; Saadati, Saeede; Zamani, Mohammad; Rezaei Kelishadi, Mahnaz; Nadery, Maryam; Doaei, Saeid; Haghighat, Neda (Frontiers in Nutrition, 2022)
Background: The findings of trials investigating the effect of conjugated linoleic acid (CLA) administration on lipid profile are controversial. Method: This meta-analysis of randomized controlled trials (RCTs) was performed to explore the effects of CLA supplementation on lipid profile. Two authors independently searched electronic databases including PubMed, Web of Science and Scopus from until March 2022, in order to find relevant RCTs. Results: In total, 56 RCTs with 73 effect sizes met the inclusion criteria and were eligible for the meta-analysis. CLA supplementation significantly alter triglycerides (TG) (WMD: 1.76; 95 % CI: -1.65, 5.19), total cholesterols (TC) (WMD: 0.86; 95 % CI: -0.42, 2.26), low-density lipoprotein cholesterols (LDL-C) (WMD: 0.49; 95 % CI: -0.75, 2.74), apolipoprotein A (WMD: -3.15; 95 % CI: -16.12, 9.81) and apolipoprotein B (WMD: -0.73; 95 % CI: -9.87, 8.41) concentrations. However, CLA supplementation significantly increased the density lipoprotein cholesterol (HDL-C) (WMD: -0.40; 95 % CI: -0.72, -0.07) concentrations. Conclusion: CLA supplementation significantly improved HDL-C concentrations, however, increased concentrations of TG, TC, LDL-C, apolipoprotein A and B.